The Effect of Profitability, Liquidity, Growth Opportunity, Risk and Tangibility Asset on Company Value with Capital Structure as Mediating Variable - Salsa Dilla Hayati; Erni Masdupi (Financial Management Studies, 2022)
The purpose of this study is to analyze how the influence of profitability, liquidity, growth opportunity, risk and asset tangibility on company value mediated by capital structure. The object of research is the infrastructure companies that listed on BEI for five years (2016-2020) period. Sampling in this research used a purposive sampling technique so that 29 sample companies were obtained and the data used were secondary data obtained from the official website of each company. The data analysis technique used is path analysis using SPSS AMOS 21.0. The results of the study stated that profitability (ROA), liquidity (CR) and asset tangibility (TANG) had a significant negative effect, growth opportunity (PER) has an insignificant positive effect and risk (DOL) has an insignificant negative effect on capital structure. Furthermore, capital structure (DAR), growth opportunity (PER) and risk (DOL) have a significant positive effect, profitability (ROA) and asset tangibility (TANG) have a significant and positive effect and liquidity (CR) has a significant and negative effect on company value. Then for testing the effect of mediation, it was found that the capital structure was not able to mediate the effect of the five independent variables on company value